A Novel Approach to Monitoring the Cs-137 Contamination of Forest Soils in Bavaria, Germany - Winkelbauer, Jennifer; Völkel, Jörg; Leopold, Matthias (DIE ERDE – Journal of the Geographical Society of Berlin, 2012)
Regarding the radioactive fission product Cs-137, particularly forest soils are hot spots of long-term contamination. Previous studies have indicated that monitoring should take account of the exceptional role of humus for Cs-137 mobility and bioavailability to effectively evaluate contamination patterns and to enhance future protection strategies in forests. As official programmes in Bavaria lack such considerations, a new monitoring project has been established together with the Bavarian State Ministry of the Environment and Public Health, focussing on humus-controlling landscape parameters (relief, vegetation etc.) as crucial core criteria. Comprising a total of 48 sites, the project provides a solid base for future research. Both the site selection process and first results are presented here.